The Effect of the Application of the Project-Based Learning Model on Early Childhood Social-Emotional Skills - Bulkis, Bulkis; Arismunandar, Arismunandar; Herman, Herman; Mustofa, Mustafa (International Journal of Multidisciplinary Approach Research and Science, 2025)
The application of the project-based learning model is one of the strategies that can be chosen to develop the principle of play while learning and make children the center of learning in early childhood education. This study aims to examine the effect of the application of the Project Based Learning (PBL) model on early childhood social-emotional skills. The research method used is quasi-experimental with a non-equivalent control group design. The research subjects consisted of early childhood children who were divided into two groups: an experimental group that applied PBL and a control group that did not use the Project Learning method. Data were collected through observation and assessment of children's social-emotional abilities before and after the intervention. The results show that the application of the PBL model significantly improves early childhood social-emotional skills compared to conventional learning methods. The implication of this study is that the PBL model can be an effective alternative in the development of early childhood social-emotional skills, which has a positive impact on their readiness to face future challenges.